2022
DOI: 10.3389/fmicb.2022.813622
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Altered the Vaginal Microbiome and Metabolome in Rabbits

Abstract: Heat stress can have an impact on parental gamete maturation and reproduction functions. According to current research, the microbial composition of the vaginal cavity is species specific. Pregnancy, menstruation, and genital diseases have been linked to the dynamics of vaginal ecology. In this study, we characterized the vaginal microbiota and metabolites after heat stress. At the phylum level, the rabbit’s vaginal microbial composition of rabbit showed high similarity with that of humans. In the Heat group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…This finding suggests that cold stress may exacerbate intestinal inflammation in mice. On the other hand, lower abundances of Family_XIII_UCG_001, Lachnospiraceae_UCG_001, Novosphingobium, RB41, and Tyzzerella have been previously reported in chronic colitis mice (Huangfu et al, 2021;Xu et al, 2021), Crohn's disease patients (Jiang et al, 2022), ulcerative colitis mice (Wang et al, 2019), heat stress-induced rabbits (Shi et al, 2022) and Alzheimer patients (Kaiyrlykyzy et al, 2022), respectively. These findings are consistent with the observations in the MC and ML groups of the current study, which indicated that cold stress may have a negative impact on mice by reducing the abundance of these four genera.…”
Section: Discussionmentioning
confidence: 93%
“…This finding suggests that cold stress may exacerbate intestinal inflammation in mice. On the other hand, lower abundances of Family_XIII_UCG_001, Lachnospiraceae_UCG_001, Novosphingobium, RB41, and Tyzzerella have been previously reported in chronic colitis mice (Huangfu et al, 2021;Xu et al, 2021), Crohn's disease patients (Jiang et al, 2022), ulcerative colitis mice (Wang et al, 2019), heat stress-induced rabbits (Shi et al, 2022) and Alzheimer patients (Kaiyrlykyzy et al, 2022), respectively. These findings are consistent with the observations in the MC and ML groups of the current study, which indicated that cold stress may have a negative impact on mice by reducing the abundance of these four genera.…”
Section: Discussionmentioning
confidence: 93%
“…Dietzia [ 46 ], Aeromicrobium [ 47 ], and Parvibacter [ 48 ] are reported as probiotic genera; the lower abundance of those three genera in sheep after calving may demonstrate the sub-healthy status of Bangor Sewa sheep. Previous research found lower abundances of Nocardioides in Salmonella-infected pigs [ 49 ]; unclassified_ Clostridia in females with osteoporosis and osteopenia [ 50 ]; Sphingobacteriaceae in obese people [ 51 ]; UCG_005 and RB41 in heat-stressed rabbits [ 52 ]; dgA_11_gut_group in rabbits model of Alzheimer disease [ 53 ]; unclassified_ Ruminococcaceae in people with hepatitis B [ 54 ]; NK4A214_group in patients with rectovaginal fistula [ 55 ]; V9D2013_group in piglets treated with Lipopolysaccharide (LPS) [ 56 ]; Prevotellaceae _UCG_004 in zearalenone-exposed mice [ 57 ]; Monoglobus in sleep-deprived mice [ 58 ]; Christensenellaceae _R_7_group in Alzheimer’s and dementia patients [ 59 ]; and Micromonospora in LPS-induced inflammation in chicks [ 60 ], which indicated that those genera were negatively related to host status. In the current results, the abundance of those genera was significantly changed in post-parturition in the genital tract of Bangor Sewa sheep, which may be closely tied to the changes in the microenvironment, including immune and hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, vaginal Lactobacillus sp. depletion is strongly associated with preterm birth (Brown et al 2019, Payne et al 2021 and is reduced by heat exposure (Song et al 2020, Shi et al 2022. Thus, ascertaining whether existing infection in pregnancy is exacerbated by heat exposure is of interest.…”
Section: Inflammation and Infectionmentioning
confidence: 99%